'Remembering the Future': Birmingham Contemporary Music Group, CBSO Centre, Birmingham. (28th September 2016) - Reynolds, Peter
Abstract : 'How do you deal with endings?', Stephen Newbould, BCMG's Artistic Director, asked a group of four composers in an interview prior to the ensemble's final concert of the season, given on 12 June. Perhaps Newbould was thinking out loud: 'Remembering the Future' marked his and Executive Producer Jackie Newbould's last event with Birmingham Contemporary Music Group, after a tenure of nearly 30 years. The CBSO Centre was packed to the rafters for this concert that featured new commissions by Luke Bedford, Richard Baker, John Woolrich and Zoë Martlew: four composers with strong connections to the group. At the suggestion of John Woolrich, in his role as Artist-in-Association with BCMG, the works were scored not for BCMG's usual larger forces but for Schoenberg's 'Pierrot' ensemble, with various additions and subtractions.